Incidence, Cytology, Gross Pathology And Histopathology Of Mammary Tumours In Dogs Of Chennai - K.R. ANJAN KUMAR; GANNE VENKATA SUDHAKAR RAO; C.BALACHANDRAN (International Journal of Pharma and Bio Sciences, 2011)
The current research work was undertaken with the objective of evaluating incidence, cytology, gross pathology and histopathology of canine mammary tumours. Population incidence was 0.39 percent. Per cent incidence was 37.25. Pure breeds were commonly affected (83.60%) with highest incidence in the Spitz (33.33%). The highest incidence of mammary tumour was found between 9-12 years of age with a mean age of 9.45 years. Intact animals were mostly affected. Posterior pair of glands was predominantly affected. NAF and FNAB revealed 66.66 per cent and 71.93 per cent malignancy. Thoracic metastasis was observed in 12.28 per cent of dogs. Tumours were staged according to TNM staging and classified on the basis of WHO classification (2002). According to Elston and Ellis grading method, out of 40 mammary gland tumours 27 were in grade I and 13 were in grade II.